Tinjauan Pemberian Kompensasi Terhadap Produktifitas Kerja Petugas Rekam Medis Di Rumah Sakit Tere Margareth Tahun 2022 - Putriana, Angelia; Erlindai, Erlindai; Febryo Siburian (Akademi Perekam dan Informasi Kesehatan Imelda, 2024)
An employee can be said to be productive if he is able to produce goods or services as expected in a short or precise time. The population of this study is medical records officers in the medical records room at RSU Tere Margareth. The sample size is 5 RM employees. The instrument in this research used interviews with respondents who were RM officers at RSU Tere Margareth. The research results showed that the distribution of respondents' answers based on interviews showed that the identification of the Main Duties of Officers in the Hospital Medical Records Unit. Tere Margareth already has a medical record service manual No. Kep/095/I/2019 as follows regarding working time arrangements at Tere Margareth Medan Hospital, divided into 2 work shifts. The performance of medical records officers at Tere Margareth Hospital has two meanings, where first, compensation and performance are directly proportional to the implementation of the quality of work of medical records officers, where from the results of interviews it was found that officers felt very happy, enthusiastic and eager to carry out their responsibilities if their work compensation was increased. However, in the second aspect, whether or not there is compensation for medical records officers, they are still enthusiastic about doing their work because it is their responsibility to do daily work without having to be lured by high compensation. This indicates that awareness of the work responsibilities of medical records officers in Tere Margareth Hospital is good. Based on the results of the research conducted, it can be concluded that RSU.Tere Margareth should pay attention to officer compensation, so that it can help in increasing the productivity of medical records officers at Tere Margareth Hospital, Medan City and officers must also be aware that without compensation, officers continue to work and are responsible for his job.